An Efficient Symbolic Interface to Constraint Based Animation Systems - Cohen, Michael; Liu, Zicheng (Proceedings of the Eurographics Workshop in Maastricht, 1995)
Symbolic methods have been used to provide a general user interface in optimization based animation systems. However, previous methods suffer from the exponential growth in the length of the symbolic expressions of the objectives, constraints and their derivatives. In this paper, we present a symbolic language which is general enough to represent common kinematic and dynamic quantities. The evaluation of these symbolic expressions and their gradients are as fast as numerical methods. In particular, the computational complexity is only a low degree polynomial compared to exponential growth of previous methods, and the optimum performance is achieved for computing the gradients of the generalized forces by extending Hollerbach's technique of computing inverse dynamics. Furthermore, in this new language the expressions are usually very small so that they can be easily typed in, therefore this method provides a general and efficient interface to optimization based linked figure animation systems.